Difference between revisions of "IGEM:Stanford/2010/Notebook/15 April 2010"

From OpenWetWare
Jump to: navigation, search
(DNA-ligand binding)
(DNA-ligand binding)
Line 15: Line 15:
  
 
Solving, we get:
 
Solving, we get:
[DNA-L] = [TotalDNA][L]/(k_on/k_off + L)
+
[DNA-L] = [TotalDNA][L] / (k_off/k_on + L)
 +
 
 +
Usually, we define the dissociation constant to be:
 +
kD = k_off/k_on
 +
 
 +
So we end up with:
 +
[DNA-L] = [TotalDNA][L] / (kD + L)

Revision as of 21:29, 15 April 2010

<html> <head> <style type="text/css"> body{background:#FFFFCC} table.menu{ background:#990000; padding:5px; color:black; } font.cell{ font-family:Verdana; font-size:14px; font-style:normal; color:#ffffff; width:99px; text-align:center; padding:0px } font.cell:hover{font-weight:bold; cursor:pointer; text-decoration:none } img{padding-bottom:5px} a.menu{text-decoration:none; color:white} a.menu:visited{text-decoration:none; color:white} </style> </head> </html>

Quad center.jpg

Journal Club 4/15/10

Presentation by ...

DNA-ligand binding

d[DNA-L]/dt = k_on*[DNA][L] - k_off*[DNA-L]

If we define: [TotalDNA] = [DNA] + [DNA-L]

Then: d[DNA-L]/dt = k_on*([TotalDNA] - [DNA-L]) - k_off*[DNA-L]

Solving, we get: [DNA-L] = [TotalDNA][L] / (k_off/k_on + L)

Usually, we define the dissociation constant to be: kD = k_off/k_on

So we end up with:

[DNA-L] = [TotalDNA][L] / (kD + L)